Microdosing: A conceptual framework for use as programming strategy for resistance training in team sports - Cuthbert, M.; Haff, G. G.; McMahon, J. J.; Evans, M.; Comfort, P. (Strength and Conditioning Journal, 2023)
Microdosing, in the context of resistance training, has increased in popularity within sporting environments where it is frequently used among strength and conditioning professionals. Although there is a clear definition for the concept within the literature, it is still commonly incorrectly used, and the extent to which microdosing has been explicitly investigated in empirical research is limited. However, there are many related research areas or themes (including programming for acute and chronic responses, programming around competition schedules, motor learning, and individualization) that indicate the potential benefits of microdosing as an overarching concept. There are also misinterpretations about the term and what microdosing entails; for example, the term microdosing is often used interchangeably with the concept of the minimum effective dose. Therefore, the aim of this review is to outline and discuss where some of these theories and concepts may or may not be appropriate for use within team sports, while also highlighting areas in which the application of microdosing requires further investigation. Although microdosing may be a relatively new term, which is considered "trendy" among practitioners, the underlying principles associated with microdosing have been expressed and investigated for a long time.